A survey of investment provisions in regional trade agreements - Vasyl Chornyi; Marianna Nerushay; Jo-Ann Crawford (World Trade Organization (WTO), 2016)
The liberalization and protection of investment flows has become an increasingly indispensable pillar of economic integration. The objective of this study is to contribute to a better understanding of the ways in which RTAs achieve such liberalization and protection. To this end, we have surveyed the investment provisions contained in 260 RTAs notified to the WTO by 31 December 2015 and in force on that date. More than half of these RTAs contain investment chapters, though they vary in terms of their substantive scope and coverage. Given the unabated increase in the number of RTAs and the push towards greater economic integration we expect this figure to further increase. The main categories of investment provisions in RTAs reviewed in the paper include the definitions of investment and investor, investment liberalization, investment protection and ISDS. Also included in our analysis are provisions supporting the investment framework, host state flexibilities, investment promotion, as well as provisions on sustainable and socially responsible investment.
Keywords: F15; F21; 330; Regional Trade Agreements; investment